Impaired Regeneration in Dystrophic Muscle—New Target for Therapy - Yanay, Nurit; Rabie, Malcolm; Nevo, Yoram (Frontiers in Molecular Neuroscience, 2020)
Muscle stem cells, known as satellite cells (SCs) have an incredible ability to regenerate which enables the maintenance and growth of muscle tissue. In response to damaging stimuli SCs are activated, proliferate, differentiate and fuse to repair or generate a new muscle fiber. However, dystrophic muscles are characterized by poor muscle regeneration along with chronic inflammation and fibrosis. Indications for SC involvement in muscular dystrophy pathologies are accumulating, but their contribution to muscle pathophysiology is not precisely understood. In congenital muscular dystrophy type-1A (LAMA2-CMD), mutations in Lama2 gene cause either complete or partial absence in Laminin-211 protein. Laminin-211 functions as a link between muscle extra cellular matrix (ECM) and two adhesion systems in the sarcolemma, one is the well-known dystrophin-glycoprotein complex (DGC) and the second is the integrin complex. Due to its protein interactions and location, Laminin-211 has a crucial role in muscle function and survival by maintaining sarcolemma integrity. In addition, Laminin-211 is expressed in SCs and suggested to have a role in SC proliferation and differentiation. Downstream to the primary defect in Laminin-211 several secondary genes and pathways accelerate disease mechanism, while at the same time there are unsuccessful attempts to regenerate as compensation for the dystrophic process. Lately Next generation-sequencing (NGS) platforms have advanced our knowledge about the secondary events occurring in various diseases, elucidate the pathophysiology, and characterize new essential targets for development of new treatment strategies. This review will mainly focus on SC contribution to impaired regeneration in muscular dystrophies and specifically new findings suggesting SC involvement in LAMA2-CMD pathology.